The role of mineral and oil resources in achieving a clean environment in emerging economies: An asymmetric analysis - Han, Zhihong; Gong, Lixin; Chen, Huiwen; Yüksel, Serhat (Elsevier Ltd, 2023)
Climate change and rising global temperatures pose significant challenges for natural resource management. While developed economies have made progress in addressing these issues, emerging economies are still striving to achieve carbon neutrality, sustainable resource use, and environmental sustainability. This research aims to identify the factors driving carbon emissions in emerging economies over the past three decades. The study establishes a long-run relationship among the factors under investigation by employing various panel diagnostic methods. Non-parametric approaches are used to account for the non-symmetric distribution of panel data. The findings reveal that natural resource components have asymmetric impacts on carbon emissions, with oil rents reducing emissions and mineral rents increasing them. Economic growth and agricultural value added are identified as significant contributors to carbon emissions in the region. On the other hand, renewable energy consumption plays a crucial role in achieving carbon neutrality targets. Gross capital formation exhibits a mixed influence on carbon emissions, being positive and significant in lower quantiles and significantly negative in upper quantiles. These estimates are robust and align with existing literature. The study recommends sustainable resource abstraction and utilization, renewable energy production and consumption improvements, and enhanced capital formation. By providing empirical evidence and policy recommendations, this research contributes to understanding the relationship between these factors and their impact on carbon emissions, facilitating effective strategies for sustainable development and environmental preservation.
Keywords: Agriculture Value Added; Capital Formation; Carbon Neutrality; Economic Growth; Emerging Economies; Natural Resources; Renewable Energy